Finanspagten og issue-linkage inden for eurosystemet - Beach, Derek (Politik, 2013)
This article claims that the reform negotiations of the euro can only be understood as a form of issue-linkage, where two groups of states (euro-winners and euro-losers) want either stricter rules for state scal behavior (euro-winners) or increased assistance mechanisms in the form of temporary aid packages or permanent transfers for countries hit by asymmetric economic shocks (euro-losers). e two issues were linked in the negotiations in 2011 and 2012, where a quid pro quo was reached, where Germany got ‘its’ Fiscal Compact that strengthened the rules for behavior in exchange for concessions on the transfer issue both in relation to accepting ECB interventions in the market to aid euro-losers facing high interest rates, and the entry into force of the permanent aid mechanism (ESM) a year ahead of schedule. Euro-losers were however only able to link the two issues when they were able to exploit their economic weakness and the risk that market pressure could result in the collapse of the euro. As this pressure has eased in the fall of 2012, the pace of reforms has slowed down, with few indications that further progress will be made on strengthening the transfer side of Economic and Monetary Union any time soon.